Optimizing pediatric preoperative fasting management: a survey of practices and real durations in Chinese hospitals - Bin Zhang; Shoudong Pan; Jijian Zheng; Bo Li; Yi Miao; Guohua Liu (BMC Anesthesiology)
Abstract Background Rational preoperative fasting can reduce the risk of regurgitation and aspiration, enhance anesthesia safety and efficiency, and mitigate the adverse effects of prolonged fasting. This study investigates the existing practices of preoperative fasting management in Chinese pediatric patients and explores the real duration of preoperative fasting. Methods This is a cross-sectional study. A questionnaire on fasting management in children was developed and an online survey was conducted among anesthesiologists. The survey mainly included the real implementation of pediatric fasting protocols, anesthesiologists’ understanding of pediatric fasting management, and the application of gastric ultrasound. Moreover, data on pediatric preoperative fasting durations were collected from different hospitals across China. Results A total of 770 questionnaires and 1285 records of preoperative fasting cases were obtained. The survey indicated variations in preoperative fasting protocols among hospitals. Most hospitals recommended fasting for clear fluids for 2 h, while the new 1-h regimen and the liberal regimen were less implemented due to concerns regarding regurgitation and aspiration risks. Fasting for breast milk, formula milk, and solid food was mainly based on traditional protocols, with fasting durations of 4 h, 6 h, and 8 h, respectively. Most anesthesiologists have experienced regurgitation and aspiration, but there were significant differences in their awareness of the prevention and prognosis of regurgitation and aspiration. Utilization of gastric ultrasound was limited, with a lack of equipment and familiarity among anesthesiologists. Real preoperative fasting durations for children were significantly longer than those recommended in the guidelines. Factors contributing to prolonged fasting were identified. Conclusions There is a big gap between preoperative fasting practices and the guidelines, and the real fasting durations of children before surgery are significantly longer than the guideline recommendations. Anesthesiologists should strengthen their understanding of preoperative fasting management in pediatric patients, master the skills of gastric ultrasound assessment, and timely address inefficiencies in pediatric preoperative fasting management.